What Is Liberatory in Feminist Theory Might Be Limiting When Administered On Paper: An Intersectional and Interlocking Antiracist Postcolonial Feminist Discourse Analysis Of the Ministry of Education's First Draft of Ontario's New Secondary 'Gender Studies' Course - Azevedo, Jessica (Université d'Ottawa | University of Ottawa, 2011)
The 2009 draft of the Ontario Ministry of Education's secondary level 'Gender Studies' course is currently undergoing review. Consequently, this study facilitates a (re)reading of this draft with and against the Miss G___ Project's’course objectives' and 'suggested topics of study' put forth on their respective website. To do so, I use an intersectional and interlocking antiracist postcolonial feminist theoretical framework to analyse both the strenghts and limitations of this first draft in relation to the feminist tenets proposed by the Miss G___ Project. In turn, I employ this theoretical framework to critically deconstruct the ways in which this draft of the policy document represents various social issues. Within a standardized Euro-Colonial white-supremacist-capitalist-patriarchal framework, the Miss G___ Project envisions this course to challenge oppression in and through the school curricula. Thus, I utilize this study to examine how 'discourses of domination' circulating within a framework can foster the institutional appropriation of Miss G__'s feminist politics as an alternative discourse throughout this particular course draft.